Improved trade-off between thermoelectric performance and mechanical reliability of Mg2Si by hybridization of few-layered reduced graphene oxides. (15th March 2019) - Kim, Gwansik; Kim, Sung Wng; Rim, Hyun Jun; Lee, Hwijong; Kim, Jeongmin; Roh, Jong Wook; Kim, Byung-Wook; Lee, Kyu Hyoung; Lee, Wooyoung
Abstract: Nanocomposites can simultaneously enhance the thermoelectric and mechanical properties of thermoelectric materials. Here, we fabricated bulks of Mg1.96 Al0.04 Si0.97 Bi0.03 with monodispersed few-layered reduced graphene oxides utilizing ultrasonic-based wet chemical pulverizing-mixing and spark plasma sintering to improve unfavorable trade-off between thermoelectric performance and mechanical reliability, which is important for commercialization. An unexpected high fracture toughness of ~1.88 MPa m 1/2 was observed due to the synergetic effect of the deflection of crack propagation, bridging, and sheet pull-out mechanisms, and a high thermoelectric figure of merit ~0.6 was obtained even for a high content (3 vol.%) of reduced graphene oxides. Graphical abstract: Unlabelled Image